PENGARUH KETIDAKPUASAN KONSUMEN DAN IKLAN PESAING TERHADAP PERILAKU PERINDAHAN MEREK PADA PRODUK HAND & BODY LOTION CITRA (STUDI PADA MAHASISWA FAKULTAS EKONOMI MANAJEMEN UNIVERSITAS ISLAM SUMATERA UTARA). - Azhar Apriandi (Universitas Islam Sumatera Utara, 2019)
The study is grounded by the decreasing of hand body Citra top brand in 3 (three) years a row which indicates the occurance phenomenon of consumer switching from hand body lotion Citra to other hand body lotion. This phenomenon is ussually called brand switching. Therefore, the problem in this study is “what are the factors that influence consumer switching from hand body lotion to another hand body lotion brand”. This study examined two independent variables; there are consumer dissatisfaction, competitor’s advertising toward brand switch behavior. The purpose of this study is to find the influence of the independent variables toward brand switching behavior. Data analysis techniques used are descriptive methods and quantitative methods. Primary data in this study were obtained by distributing questionnaires, measuring using a likert scale and processed systematically using the Statistical For Product and Service solution (SPSS) version 20 program. The test used in this study is validity test, reliabiliy test, multiple linear regression test, classic assumption test, t test, f test, and determination. Consumer dissatisfaction has a positive and significant effect on brand switching behavior because that is 2.326 1.993. Competitor advertising has a positive and significant effect on brand switching behavior because that is 4.163 1.993. Consumer dissastifaction and competitor advertising simultaneously have a positive and significant effect on brand switching behavior because that is 38.061 3.11 and a significant level for the F test equal to 0.000 0.05 means that consumer dissatisfaction and competitor advertising have a positive and significant effect on brand switching behavior. Based on the overall result of the study, it can be concluded that partially and simultaneously consumer dissatifaction and cocompetitor advertisor have a positive and significant effect on brand switching behavior in product hand body lotion Citra.